2020
DOI: 10.1080/19490976.2020.1792256
|View full text |Cite
|
Sign up to set email alerts
|

Modifying macronutrients is superior to microbiome transplantation in treating nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the leading cause of chronic liver injury and liver transplantation in Western countries. The pathogenesis of NAFLD includes overnutritionassociated metabolic syndrome or the improper consumption of dietary macro-and micronutrients that either support or prevent disease development. This altered nutrient landscape has been linked to shifts within the gut microbiota which can exacerbate liver pathology and the progression of NAFLD. Treatment goals for NAFLD target lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…The exact mechanisms of FMT are not fully understood and there are probably multiple routes of beneficial effects, e.g., through microbial modulation of the phageome, or activation of the bile-acid–FXR–FGF-19 pathway [33]. FMT affected liver DNA methylation in patients with MASLD [34], indicating an epigenetic regulatory effect of microbiota on genes relevant for metabolism. FMT from lean healthy donors to obese patients with type 2 diabetes mellitus led to reduced LDL and liver stiffness, when combined with lifestyle interventions [35].…”
Section: Metabolic Dysfunction-associated Steatotic Liver Diseasementioning
confidence: 99%
“…The exact mechanisms of FMT are not fully understood and there are probably multiple routes of beneficial effects, e.g., through microbial modulation of the phageome, or activation of the bile-acid–FXR–FGF-19 pathway [33]. FMT affected liver DNA methylation in patients with MASLD [34], indicating an epigenetic regulatory effect of microbiota on genes relevant for metabolism. FMT from lean healthy donors to obese patients with type 2 diabetes mellitus led to reduced LDL and liver stiffness, when combined with lifestyle interventions [35].…”
Section: Metabolic Dysfunction-associated Steatotic Liver Diseasementioning
confidence: 99%
“…This improvement can be explained by changes in GM that increase butyrate levels and reduce pro-inflammatory factors (i.e., IL-1, IL-6 or TNFα), promoting an anti-inflammatory microenvironment [ 74 ]. However, Mitsinikos et al showed that FMT may not be as advantageous as dietary modifications, given that FMT from mice receiving dietary interventions to rats with NASH did not improve histological activity [ 98 ].…”
Section: Fmt and Nafldmentioning
confidence: 99%